Epidemiology and distribution of cruciate ligament injuries in children and adolescents, with an analysis of risk factors for concomitant meniscal tear - Zhi, Xinwang; Wen, Zhicheng; Zhang, Jiexin; Lai, Dongbo; Ye, Huilan; Wu, Jianping; Li, Jintao; Shao, Yan; Canavese, Federico; Zeng, Chun; Xu, Hongwen (Frontiers in Pediatrics, 2024)
Introduction To investigate the epidemiological features and prevalence of cruciate ligament injuries (CLI) in children and adolescents, and to examine the potential risk factors associated with concomitant meniscal tear (MT) among this population. Methods The demographic data and injury details of children and adolescents with CLI from Southeast China were analyzed to describe their distribution characteristics, alongside an analysis of the prevalence of MTs, the most frequent complication. In addition, binary logistic analysis was employed to ascertain the risk factors linked to MT in individuals suffering from CLI. Results A total of 203 patients with CLI (n = 206) met the inclusion criteria, with a male-to-female ratio of 2.3:1. Notably, a higher proportion of females were aged ≤16 years old compared to males, who predominated in patients aged >16 years (P = 0.001). Among children and adolescents, anterior cruciate ligament (ACL) injuries were the primary type of CLI, accounting for 88.18% (179/203) of all cases. The majority of cases (132/203, 65.02%) were sustained during sports activities, and sprains were the predominant mechanism of injury (176/203, 86.7%). Additionally, the most common associated injury was an MT (157/203, 77.34%). The posterior horn is the most frequently affected site for both medial MT (62.93% out of 73 cases) and lateral MT (70.19% out of 73 cases). Moreover, vertical tears constituted the majority of medial MTs (59.48% out of 116 cases). Furthermore, patients with a higher BMI faced an increased risk of associated MT in comparison to non-overweight patients (88% vs. 73.86%; P = 0.038). Each increase in BMI unit was linked with a 14% higher probability of associated MT occurrence in children and adolescents with CLI (OR = 1.140; P = 0.036). Discussion ACL injuries are a common form of knee ligament injury among children and adolescents, especially those over the age of 16, and are often the result of a sprain. Meniscal posterior horn injury is the most commonly associated injury of youth with CLI. Additionally, overweight or obese people with CLI are at a greater risk of developing MT.